Serpúlidos (Polychaeta: Serpulidae) del Caribe noroccidental: Hydroides y Serpula - Bastida-Zavala, José Rolando (2000)
From the study of more than 450 specimens of Hydroides and Serpula, 12 species from the Grand Caribbean Region were identified and characterized. Eight species were collected along the shores of the Yucatan Peninsula and five were found in other localities in the Gulf of Mexico, seven others are from Cuba and comments on type specimens of five species are also included. One morphometric analysis made on Hydroides mucronatus Rioja and Hydroides cf. mucronatus, indicated several differences among them. Comments on all species are also included